The ignition of the bio water-coal fuel particles based on coals of different degree metamorphism. (15th June 2020) - Kuznetsov, G.V.; Malyshev, D. Yu; Kostoreva, Zh.A.; Syrodoy, S.V.; Gutareva, N. Yu.
Abstract: The results of the experimental studies of the processes of ignition of a new class of the fuels — bio water-coal fuel (Bio WCF) have been given, the main components of which are coals of various degrees of metamorphism, water and forest combustible material (FCM). It has been established that the addition of FCM to the composition of the water-coal suspension stabilizes the combustion process and leads to a decrease in the total induction period by 10–15%. The experiments have been conducted on the equipment that provides a fairly low level of error when registering the main characteristics of heat and mass transfer processes occurring together with ignition of the bio water-coal fuel particles. According to the results of the experiments, it has been established that the ignition of such fuel particles takes place in the gas phase, and during the combustion of volatiles a flame sphere is formed, the characteristic dimensions of which exceed the particle diameter by 2–3 times. The main result of the experimental researches is the substantiation of the possibility of using forest combustible fuel in the form of an additive that accelerates and stabilizes the process of initiating combustion of such a composite fuel. Graphical abstract: Image 1 Highlights: Experimentally studied ignition of a new class of fuel particles - bio-coal-water fuel. We found that adding forest fuel to a coal-water slurry significantly reduces the ignition delay time. We found that the type of coal significantly affect the mechanism of ignition particles bio - coal-water fuel. We have established the integral characteristics of the processes of bio-ignition of coal-water fuel particle. We have shown that the type of forest fuel has no strong effect on the rate of bio-coal-water fuel ignition.